Penthorum chinense Pursh. extract attenuates non-alcholic fatty liver disease by regulating gut microbiota and bile acid metabolism in mice. (10th August 2022) - Li, Xiaoxi; Zhao, Wenwen; Xiao, Meng; Yu, Lan; Chen, Qijun; Hu, Xiaolu; Zhao, Yimeng; Xiong, Lijuan; Chen, Xiaoqing; Wang, Xing; Ba, Yinying; Guo, Qiang; et al.
Abstract: Ethnopharmacological relevance: Penthorum chinense Pursh. (PCP) is commonly used as a Miao ethnomedicine and health food for liver protection in China. Gansukeli (WS3–B-2526-97) is made from the extract of PCP (PCPE) for the treatment of viral hepatitis. In recent years, PCPE has been reported in the treatment of non-alcoholic fatty liver disease (NAFLD), however its potential mechanism is not fully elucidated. Aim of the study: To investigate the ameliorating effect of PCPE on high-fat diet (HFD)-induced NAFLD mice and demonstrate whether its protective effect is gut microbiota dependent and associated with bile acid (BA) metabolism. Materials and methods: The alleviating effect of PCPE on NAFLD was conducted on male C57BL/6J mice fed an HFD for 16 weeks, and this effect associated with gut microbiota dependent was demonstrated by pseudo-germfree mice treated with antibiotics and fecal microbiota transplantation (FMT). The composition of the gut microbiota in the cecum contents was analyzed by 16S rRNA sequencing, and the levels of BAs in liver and fecal samples were determined by UPLC/MS-MS. Results: The results showed that administration of PCPE for 8 weeks could potently ameliorate HFD-induced NAFLD and alleviate dyslipidemia and insulin resistance. Moreover, PCPE treatment alleviated gut dysbiosis, especially reducing the relative abundance of bile salt hydrolase (BSH)-producing bacteria. Furthermore, PCPE significantly increased the levels of taurine-conjugated BAs in feces, such as tauro-β-muricholic acid (T-βMCA), tauroursodesoxycholic acid (TUDCA), and taurochenodeoxycholic acid (TCDCA), and increased hepatic chenodeoxycholic acid (CDCA). The protein and mRNA expression of farnesoid X receptor (FXR) and fibroblast growth factor 15 (FGF15) were decreased in intestine, increased taurine-conjugated BAs inhibited the intestinal signaling pathway, which was associated with increased genes expression of enzymes in the alternative BA synthesis pathway that reduced the levels of cholesterol. The increased CDCA produced via the alternative BA synthesis pathway promoted hepatic FXR activation and BA excretion. Conclusion: Our study is the first time to demonstrate that PCPE could ameliorate NAFLD in HFD-induced mice by regulating the gut microbiota and BA metabolism, and from a novel perspective, to clarify the mechanism of PCPE in NAFLD. Graphical abstract: Image 1 Highlights: Penthorum chinense Pursh. extract (PCPE) alleviating NAFLD in HFD-fed mice is gut microbiota dependent. PCPE increases ileum conjugated bile acids levels via reducing the abundance of bile salt hydrolase-producing bacteria. PCPE reduces liver lipid deposition by regulating the key genes FXR, FGF15, CYP27A1, and BSEP in bile acid metabolism.